Contractarian Libertarianism of Jan Narveson. Is It Still Libertarianism? (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
This chapter aims at presenting and scrutinizing a contractarian approach to libertarianism, which has been proposed by a Canadian philosopher, Jan Narveson, known as the main proponent of so-called contractarian libertarianism. The chapter begins with the short introduction followed by “Assumptions,” discussing Narveson’s understanding of morality, his critique of Rawlsian methodology and his view on natural law and natural rights. Afterwards, “Social contract: justification, procedure, motives” presents such elements in the philosophy of Narveson as advantages of contractarianism, levels of the social contract and its status, as well as motives of parties being subject to the social contract. The third part, entitled “Critics vs. Narveson” touches on a critical discussion of the subject by other theorists (Tibor R. Machan, John T. Sanders, Leo Groarke). The last section, “Is the Contractarianism of Narveson Libertarianism?” presents the thesis that Narveson’s contractarianism is not a justified basis of libertarianism. Albeit he comes to conclusions agreeable to libertarianism, his philosophy is better labeled as laissez-faire.